Periurethral anaerobic microflora of healthy girls. - Bollgren, I (1979)
The periurethral anaerobic and aerobic microfloras were investigated in 18 healthy premenarcheal girls, 5 to 14 years of age, by using a quantitative sampling method. Colonization of the female periurethral area with enterobacteria seems to be an important step in the development of urinary tract infections, and the present study was undertaken as a stage in elucidating factors that might control the establishment of urinary tract pathogens periurethrally. The study showed that obligate anaerobic bacteria constituted 95.0% (standard error, +/- 5.8%) of the total colony-forming units per square centimeter of periurethral area. An average of 7.0 different anaerobic and 2.7 different aerobic strains per specimen was obtained. The flora was dominated by anaerobic gram-positive cocci and gram-positive rods, whereas anaerobic gram-negative rods comprised a minor part. The most commonly encountered anaerobic isolates were peptococci and peptostreptococci, propionibacteria, bifidobacteria, eubacteria, and bacteroides in decreasing order of frequency. The aerobic flora consisted most commonly of nonhemolytic streptococci and diphtheroids. The findings suggest that the periurethral microenvironment is a distinctive ecological niche, separate from the fecal and skin biotas, although it has some characteristics in common with the vaginal flora.